Evaluating the addition of starry triggerfish (Abalistes stellaris) bone charcoal as a feed supplement to the growth performance and intestinal villi length of nile tilapia (Oreochromis niloticus) - Azwar Thaib; Lia Handayani; Ardila Hanum; Nurhayati Nurhayati; Faisal Syahputra (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2021)
Nile tilapia is a freshwater fish that is widely cultivated in Indonesia. During its development, tilapia aquaculture has constraints such as low growth rates. Therefore, it is necessary to add a feed additive to the feed in the form of charcoal. Charcoal is an adsorbent that has high absorption so that the addition of charcoal in the feed can increase the absorption of nutrients of tilapia. A 45-days trial was conducted to determine the percentage of addition of triggerfish bone charcoal (Abalistes stellaris) as a feed supplement that affect the growth performance and intestines of tilapia. The research design was a non-factorial Completely Randomized Design (CRD) with 4 treatments and 2 replications as treatments including: treatment A (control), B (addition of 1%charcoal), C (addition of 2% charcoal) and D (addition of 3% charcoal). A total of 240 tilapia fingerlings (5-7 cm) were used and placed in 8 aquariums then filled with 72 liters of water. Providing adlibitum (unlimited) feed with a frequency of 2 times a day. The ANOVA test showed that the addition of triggerfish bone charcoal (A. stellaris) in the feed was not significantly different (P 0.05) in weight growth, absolute length and daily length growth but it was significantly different (P 0.05) in feed conversion ratio and the efficiency of feed utilization. Based on result, it was concluded that the addition of 3% charcoal was the best treatment which gave the lengthiest of villi which was increasing the length of the intestinal villi to 71.11 m from the initial length of 162.22 m. easel at 233.33 m, showed the highest feed conversion ratio value and feed efficiency (1.12 %, 89.6%).Keywords:CharcoalFish boneIntestinal histologyStarry triggerfish